Pengaruh Metode Pembelajaran Karya Wisata terhadap Kemampuan Sains pada Anak Usia 5-6 Tahun di TK Hasanah Lolo Kecil Kecamatan Bukit Kerman - Orca Dwi Aprita; Indryani Indryani; Akhmad Fikri Rosyadi (Journal on Education, 2023)
Field trips are a method of carrying out learning activities in PAUD institutions by directly observing the world according to reality, which includes humans, animals, plants, and other objects. The purpose of this study was to determine the effect of the field trip learning method on science abilities in children aged 5-6 years at Hasanah Lolo Kecil Kindergarten, Bukit Kerman District. This research is a type of quantitative research using experimental methods. This research includes Pre-Experimental Design. The population of this research is 12 children, the sample of this research is 12 children. The sample collection technique uses the Nonprobability sampling technique. Data collection techniques in this study used observation. Data analysis used in this research is t-test, homogeneity test, normality test, hypothesis test. Based on the results of the analysis on the pre test and post test, the value of t count is 6.02427 when compared to t table 1.7959, so t count > t table, so it can be concluded that there is an influence of the field trip learning method on science abilities in children aged 5-6 years in kindergarten Hasanah Small Lolo District of Bukit Kerman.